Integrating sustainability and resilience in agri-food supply chains - Andrés Mauricio Paredes-Rodríguez; Juan Pablo Orejuela-Cabrera; Juan Carlos Osorio-Gómez (International Journal of Sustainable Engineering)
Sustainability has become part of agri-food supply chain management via short-, medium- and long-term strategies that balance different economic, social and environmental performance functions. However, within the supply chain, events known as risks are generated. These risks become obstacles to achieving sustainability. From a risk perspective, resilience must be developed within the supply chain to manage disruptions throughout the network and achieve the expected performance associated with different sustainability metrics. Although sustainability and resilience have been studied within the context of agrifood supply chains, each presents challenges when addressed independently. Consequently, several authors argue that it is essential to investigate the interaction between these two concepts. Thus, this research proposes a framework for managing the supply chain that integrates both resilience and sustainability into the food supply. The methodology used in the study is based on a literature search following the PRISMA protocol. This research reveals a significant overlap between the indicators used to measure both resilience and sustainability within agrifood supply chains, illustrating that these concepts can be assessed from multiple dimensions. Building on this premise, a framework is proposed that integrates both sustainability and resilience, aiming to support a comprehensive and multidimensional understanding of agrifood supply chain management.